Uma proposta metodológica para construção de índices de vulnerabilidade social usando Análise Multivariada de Dados - Rech, Bruno Luiz Schuster (2024)
The present paper proposes a methodology for the construction of social vulnerability indexes based on statistical multivariate methods. Using data from Cadastro Único, factor analysis and clustering analysis were applied with the intention of generating social vulnerability indexes, comparing those with the Índice de Vulnerabilidade Social das Famílias Paranaenses (IVFPR) aiming to validate the proposed methodology. This validation occured through a case study developed in the city of Foz do Iguaçu - PR, showing the efficacy in identifying regions with higher levels of social vulnerability and offering guidance to inclusive public policies for these families in state of social vulnerability